PENJATUHAN SANKSI PIDANA BAGI ANAK PELAKU TINDAK PIDANA PERBARENGAN (CONCURSUS), (STUDI KASUS PUTUSAN NOMOR : 445/PID. SUS/2011/PN.KAG). - Anggraini, Devi; Muthahir, Ardi; Kristiani, Rheza Dwi (LPPM Universitas Bina Insan, 2021)
Abstract Concursus is criminal burden.This contradicts the concept of child protection which is currently an interesting issue in Indonesia. On the one hand, burdensome crime means giving special suffering to the perpetrator of a criminal act and on the other hand protection of children provides something that educates naughty children, not giving suffering to children. Talking about criminal acts, of course, cannot be separated from criminal sanctions. Criminal action correlates with criminal sanctions inherent in criminal acts. The problem of determining criminal sanctions is always related to views on the purpose of punishment. This study discusses the legal considerations of judges in imposing criminal sanctions for children of concurrent criminal offenders in the case verdict number: 445 / Pid. Sus / 2011 / PN.KAG and the suitability of the imposition of criminal sanctions in the case of decision number: 445 / Pid. Sus / 2011 / PN.KAG with the aim of punishment. This research was conducted with a focus related to the problems in this study. This research was conducted by studying the data obtained from the results of the literature review, namely the decision number: 445 / Pid. Sus / 2011 / PN.KAG, books, and legislation related to the problems in this thesis. This research is a normative legal research. In this study it can be argued that a child commits a crime due to environmental influences, both internal and external. Prison punishment is not the main effort to convict children. Prison sentences are not effective in improving children's behavior or preventing naughty children from doing their actions again.